2022
DOI: 10.2196/37600
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Implementation of a User-Driven, Web-Based Application Designed to Improve Sexual Health Knowledge and Communication Among Young Zambians: Mixed Methods Study

Abstract: Background Digital health interventions show promise in improving the uptake of HIV services among adolescents and young people aged 15 to 24 years in sub-Saharan Africa. Objective This study aimed to pilot-test a theory-based, empirically grounded web-based application designed to increase condom-related knowledge, sexual and reproductive health (SRH) communication, and healthier choices among young Zambians. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…With the increasing popularity of mobile based interventions with young people, they promise to improve SRH services utilisation young people. In the present review, four studies utilised mHealth interventions to improve SRH outcomes ( 33 , 35 , 61 , 62 ). Nuwamanya and colleagues, 2020, used an internet based mobile phone application to improve the use of modern contraceptive methods ( 35 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the increasing popularity of mobile based interventions with young people, they promise to improve SRH services utilisation young people. In the present review, four studies utilised mHealth interventions to improve SRH outcomes ( 33 , 35 , 61 , 62 ). Nuwamanya and colleagues, 2020, used an internet based mobile phone application to improve the use of modern contraceptive methods ( 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…Gichangi and colleague, 2022, reported that there was a statistically significant drop in the average absolute number of contraceptives myths and misconceptions believed by the mHealth intervention arm between baseline and endline ( 33 ). Sharma and colleagues 2022, reported that at the endline, an mHealth intervention resulted in higher level of knowledge related to condoms and on wearing condoms correctly ( 61 ). According to Macharia and colleagues, (2023), there was a statistically significant difference in the total knowledge scores in the mHealth intervention group compared with the control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The school is an ideal place to conduct sex education for college students. It will be crucial in standardizing HIV/AIDS health education, expanding coverage and improving the effect of publicity by offering HIV/AIDS health education classes, and using the new Internet media to publicize HIV/AIDS prevention and control as well as improve knowledge and other measures [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, as infecções sexuais são altamente contagiosas e podem ser transmitidas facilmente de uma pessoa para outra. Por isso, a prevenção é essencial para proteger não apenas a saúde individual, mas também de toda a comunidade (SHARMA, A., et al, 2022).…”
Section: )unclassified